PENGARUH FAKTOR – FAKTOR FINANSIAL TERHADAP KINERJA KEUANGAN PADA BANK UMUM KONVENSIONAL BUKU 2 - Arya Pratama Putra; Fajar Syaiful Akbar (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research was conducted to analyze Financial Factors on the Financial Performance of conventional general banking companies BUKU 2 registered by Financial Services Authority of Indonesia. The population are banking companies BUKU 2 registed by Financial Services Authority of Indonesia for the 2016-2019 period. Total population of registered banking companies BUKU 2 is 35 companies. This research uses purposive sampling technique. From the total of population, only 18 conventional general banking companies BUKU 2 meet the be a sample criteria. The data analysis technique used is multiple linear regression analysis. Based on the results of the study “The Effect of Financial Factors on Financial Performance in Convenventional Commercial Banks BUKU 2” the following conclusions were obtained: Capital Adequacy Ratio doesn’t affect the Retun On Asset, Loan to Deposit Ratio does not affect the Return On Asset, Non Performing Loan has an effect on the Return On Asset, Operational Efficiency Ratio has an effect on the Return On Asset, Net Interest Margin has an effect on the Return On Asset, and Firm Size does not affect the Retun On Asset at Conventional Commercial Banks BUKU 2.